Mesostructural paragenesises of the southeastern part of the Ebeta antiform (Northern Kazakhstan) - B. G. Golionko; O. A. Artemova (Известия высших учебных заведений: Геология и разведка)
Data on a geoiogical structure and evolution of mesostructural complexes of a southeast part of the Ebeta antiformhas been provided. Multistage nature of the deformations and a metamorphism of a Mamyt metamorphic complex and its frame have been established. Early stages of de formations and a metamorphism of granulate and amphibolitic facies of Mamyt complex have been shown to be connected with its internal evolution. In a frame of a complex, three stages of deformations have been established. The first stage of forma tion of sheath and isoclinal folds occurred before formation of structure of the area and probably has late Precambrian age. The second, marked by formation of asymmetric folds of the western vergence, corresponds to Paieozoic stage of removal of the Mamyt complex; ophiolite obduction and formation of fold and thrust structure. The third stage of shear movements fixed both in Mamyt metamorphic complex and in its frame, brought to formation of late shear folds with steeply dipping hinges, having complicated earlier created structure.